2022
DOI: 10.1002/ijc.34012
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein trajectories and the risk of all cancer types: A prospective cohort study

Abstract: A single CRP measurement is insufficient to examine the association of long-term patterns of CRP concentration with cancer risk. We prospectively examined the relationship between CRP trajectory patterns and new-onset cancers among 52 276 participants. Latent mixture modeling was used to identify CRP trajectories. Cox proportional hazards regression models were used to evaluate the association between CRP trajectory patterns and the risk of overall and specific-site cancer. Four CRP trajectories patterns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…As previously stated ( 17 ), this study was based on the Kailuan Study, a community-based ongoing cohort study performed in Tangshan city. The current study investigated the risk factors for chronic diseases such as cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously stated ( 17 ), this study was based on the Kailuan Study, a community-based ongoing cohort study performed in Tangshan city. The current study investigated the risk factors for chronic diseases such as cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The fasting triglyceride-glucose (TyG) index is a simple and cost-effective way to detect IR ( 14 ) compared to the gold standard hyperinsulinemic-euglycemic glucose clamp approach ( 15 ). High-sensitivity C-reactive protein (hs-CRP), also known as CRP assessed by high-sensitivity assays, is a typical protein produced in response to inflammation, infection, and tissue damage that has been linked to chronic disorders such as cardiovascular disease (CVD) and cancer ( 16 , 17 ). Based on the evidence above, we assume that the close association of abdominal obesity rather than general obesity with CRC risk might be mediated by IR and inflammation, which, to our knowledge, has never been systematically explored in large-scale prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…Two meta‐analyses have confirmed that CRP is linked to a higher risk of incident cardiovascular events and can also predict future cardiovascular and all‐cause mortality in individuals with type‐2 diabetes 52,53 . CRP is also a potential biomarker for overall cancer because it plays a role in the occurrence of various types of cancer 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies implicating CRP as a possible prognostic factor in solid tumors. 12,[34][35][36][37][38] CRP is a non-specific marker of acute phase inflammatory response. It is synthesized primarily in liver hepatocytes and stimulated by pro-inflammatory cytokines (IL-6, IL-1, and tumor necrosis alpha).…”
Section: Discussionmentioning
confidence: 99%